Effects of sphingolipids overload on red blood cell properties in Gaucher disease - Dupuis, Lucie (J Cell Mol Med, 2020)
Gaucher disease (GD) is a genetic disease with mutations in the GBA gene that encodes glucocerebrosidase causing complications such as anaemia and bone disease. GD is characterized by accumulation of the sphingolipids (SL) glucosylceramide (GL1), glucosylsphingosine (Lyso‐GL1), sphingosine (Sph) and sphingosine‐1‐phosphate (S1P). These SL are increased in the plasma of GD patients and the associated complications have been attributed to the accumulation of lipids in macrophages. Our recent findings indicated that red blood cells (RBCs) and erythroid progenitors may play an important role in GD pathophysiology. RBCs abnormalities and dyserythropoiesis have been observed in GD patients. Moreover, we showed higher SL levels in the plasma and in RBCs from untreated GD patients compared with controls. In this study, we quantified SL in 16 untreated GD patients and 15 patients treated with enzyme replacement therapy. Our results showed that the treatment significantly decreases SL levels in the plasma and RBCs. The increased SL content in RBCs correlates with abnormal RBC properties and with markers of disease activity. Because RBCs lack glucocerebrosidase activity, we investigated how lipid overload could occur in these cells. Our results suggested that SL overload in RBCs occurs both during erythropoiesis and during its circulation in the plasma.